Desenvolvimento de competências laborais em um ambiente de aprendizagem social: um estudo de caso com uma família de rendeiras em Alcaçuz/RN - Ferreira, Thaís Barbosa (2014)
The aim of this study was to analyze how de labor competences happen in a social learning environment, in a family of artisans that work with bilro. This is a qualitative research and the chosen method was the thematic oral history. The subjects of this study were seven artisans that work with bilro, aged between 32 and 73 years old, belonging to the same family and residents of Alcaçuz Thorp, situated at Nísia Floresta city, Rio Grande do Norte, Brazil. The theoretical references approached the handicraft and the artisan work as member of a community of practice, the social learning, community of practice and situated learning and labor competences. In the analysis, it was used data collected through observation, which resulted in a field diary, interviews and videos recorded by the researcher, in which parts of it resulted in a final video. The results showed that the learning of the artisans involved in this research happened through the social learning, inside their own family, characterized as community of practice, and it was stimulated by the legitimate peripherical participation. In this context, they developed specifics labor competences to exert their activity based on the functional, behavioral, ethical and political components, from Paiva model (2013). The results presented in this study, aim to contribute with the preservation of the labor practice, as well as indicate possible contributions for society, government, agencies related to the handicraft and the very activity.